"3D Fusion" Echocardiography Improves 3D Left Ventricular Assessment: Comparison with 2D Contrast Echocardiography. Issue 2 (13th June 2014) - Augustine, Daniel; Yaqub, Mohammad; Szmigielski, Cezary; Lima, Eduardo; Petersen, Steffen E.; Becher, Harald; Noble, J. Alison; Leeson, Paul
<x xml:space="preserve">Abstract</x> Background Three‐dimensional fusion echocardiography (3DFE) is a novel postprocessing approach that utilizes imaging data acquired from multiple 3D acquisitions. We assessed image quality, endocardial border definition, and cardiac wall motion in patients using 3DFE compared to standard 3D images (3D) and results obtained with contrast echocardiography (2DC). Methods Twenty‐four patients (mean age 66.9 ± 13 years, 17 males, 7 females) undergoing 2DC had three, noncontrast, 3D apical volumes acquired at rest. Images were fused using an automated image fusion approach. Quality of the 3DFE was compared to both 3D and 2DC based on contrast‐to‐noise ratio (CNR) and endocardial border definition. We then compared clinical wall‐motion score index (WMSI) calculated from 3DFE and 3D to those obtained from 2DC images. Results Fused 3D volumes had significantly improved CNR (8.92 ± 1.35 vs. 6.59 ± 1.19, P < 0.0005) and segmental image quality (2.42 ± 0.99 vs. 1.93 ± 1.18, P < 0.005) compared to unfused 3D acquisitions. Levels achieved were closer to scores for 2D contrast images (CNR: 9.04 ± 2.21, P = 0.6; segmental image quality: 2.91 ± 0.37, P < 0.005). WMSI calculated from fused 3D volumes did not differ significantly from those obtained from 2D contrast echocardiography (1.06 ± 0.09 vs. 1.07 ± 0.15, P = 0.69), whereas unfused images produced significantly more variable results (1.19 ± 0.30). This was confirmed by a better intraclass correlation coefficient (ICC 0.72; 95% CI 0.32–0.88) relative to comparisons with unfused images (ICC 0.56; 95% CI 0.02–0.81). Conclusion 3DFE significantly improves left ventricular image quality compared to unfused 3D in a patient population and allows noncontrast assessment of wall motion that approaches that achieved with 2D contrast echocardiography.